Effects of Parental Warmth and Behavioral Control on Adolescent Externalizing and Internalizing Trajectories Across Cultures - W. Andrew Rothenberg (2020)
© 2020 Society for Research on Adolescence We investigated the effects of parental warmth and behavioral control on externalizing and internalizing symptom trajectories from ages 8 to 14 in 1,298 adolescents from 12 cultural groups. We did not find that single universal trajectories characterized adolescent externalizing and internalizing symptoms across cultures, but instead found significant heterogeneity in starting points and rates of change in both externalizing and internalizing symptoms across cultures. Some similarities did emerge. Across many cultural groups, internalizing symptoms decreased from ages 8 to 10, and externalizing symptoms increased from ages 10 to 14. Parental warmth appears to function similarly in many cultures as a protective factor that prevents the onset and growth of adolescent externalizing and internalizing symptoms, whereas the effects of behavioral control vary from culture to culture.